The way [videorecording (DVD)] - Estevez, Emilio, 1962-; Sheen, Martin; Unger, Deborah Kara; Nesbitt, James, 1965- (ARC Entertainment, 2011)
Tom goes to St. Jean Pied de Port, France, to collect the remains of his adult son, who was killed in the Pyrenees in a storm while walking the Camino de Santiago. Rather than return home, Tom decides to embark on the historical pilgrimage to honor his son's desire to finish the journey. What Tom doesn't plan on is the profound impact the journey will have on him as he begins to learn the difference between the life one lives and the life one chooses.